2013
DOI: 10.1080/14786419.2012.711327
|View full text |Cite
|
Sign up to set email alerts
|

A new cyclonerol derivative from a marine-derived fungusAscotrichasp. ZJ-M-5

Abstract: A new sesquiterpene, ascotrichic acid (1), was isolated from a marine-derived fungus Ascotricha sp., together with the other two known analogues, cyclonerodiol (2) and 10(Z)-cyclonerotriol (3). Its structure was established by spectroscopic methods (1D and 2D NMR, HR-ESI-MS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Compared to the rice culture control at the same culture condition, the HPLC finger-print of the EtOAc extract of the culture with sodium butyrate (10 µM) in rice medium showed new peaks at about 15, 31, and 38 min ( Figure 1A), and the main peaks of the harziane diterpenoids at 33-42 min ( Figure 1B) disappeared. Chemical investigation of the EtOAc extract led to the isolation of three new terpenoids, including one novel chlorinated cleistanthane diterpenoid, harzianolic acid A (1), one harziane diterpenoid, harzianone E (2), and one cyclonerane sesquiterpenoid, 3,7,11-trihydroxy-cycloneran (3), together with 11 known sesquiterpenoids, including eight cyclonerane sesquiterpenoids, methyl 3,7-dihydroxy-15cycloneranate (4) (Song et al, 2018), catenioblin C (5) (Wu et al, 2012), ascotrichic acid (6) (Xie et al, 2013), cyclonerotriol (7) (Kasitu et al, 1992), (10E)-12-acetoxy-10-cycloneren-3,7-diol (8) (Fang et al, 2018), cyclonerodiol (9) (Nozoe et al, 1970), cyclonerodiol oxide (10) (Fujita et al, 1984) and epicyclonerodiol oxide (11) (Fujita et al, 1984), one african sesquiterpenoid, ophioceric acid (12) (Reátegui et al, 2005), and two acoranetype sesqiuterpenoids, ent-trichoacorenol (13) (Brock and Dickschat, 2011) and trichoacorenol (14) (Huang et al, 1995) (Figure 2). These results revealed that the original main products harziane diterpenoids were replaced by cyclonerane sesquiterpenoids.…”
Section: Chemical Identification Of the Isolated Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to the rice culture control at the same culture condition, the HPLC finger-print of the EtOAc extract of the culture with sodium butyrate (10 µM) in rice medium showed new peaks at about 15, 31, and 38 min ( Figure 1A), and the main peaks of the harziane diterpenoids at 33-42 min ( Figure 1B) disappeared. Chemical investigation of the EtOAc extract led to the isolation of three new terpenoids, including one novel chlorinated cleistanthane diterpenoid, harzianolic acid A (1), one harziane diterpenoid, harzianone E (2), and one cyclonerane sesquiterpenoid, 3,7,11-trihydroxy-cycloneran (3), together with 11 known sesquiterpenoids, including eight cyclonerane sesquiterpenoids, methyl 3,7-dihydroxy-15cycloneranate (4) (Song et al, 2018), catenioblin C (5) (Wu et al, 2012), ascotrichic acid (6) (Xie et al, 2013), cyclonerotriol (7) (Kasitu et al, 1992), (10E)-12-acetoxy-10-cycloneren-3,7-diol (8) (Fang et al, 2018), cyclonerodiol (9) (Nozoe et al, 1970), cyclonerodiol oxide (10) (Fujita et al, 1984) and epicyclonerodiol oxide (11) (Fujita et al, 1984), one african sesquiterpenoid, ophioceric acid (12) (Reátegui et al, 2005), and two acoranetype sesqiuterpenoids, ent-trichoacorenol (13) (Brock and Dickschat, 2011) and trichoacorenol (14) (Huang et al, 1995) (Figure 2). These results revealed that the original main products harziane diterpenoids were replaced by cyclonerane sesquiterpenoids.…”
Section: Chemical Identification Of the Isolated Compoundsmentioning
confidence: 99%
“…Mosher's method (Cao et al, 2014) was tried to determine the absolute configuration of C-7 but failed. Fortunately, a literature survey revealed that the coisolated cyclonerane-type compounds (4-9) and many other similar natural compounds have been reported the same absolute configurations as 2S,3R,6R,7R (Hanson et al, 1975;Kasitu et al, 1992;Li et al, 2007;Wu et al, 2012;Xie et al, 2013;Zhang et al, 2017;Fang et al, 2018;Song et al, 2018). Therefore, based on the biogenetic considerations, compound 3 was proposed to have the same absolute configuration (2S,3R,6R,7R) as the co-isolated compound 9, which was also supported by their similar OR between 3 ([α] 22 D -29.9 (c 1.00, CHCl 3 )) and 9 ([α] 22 D -26.6 (c 1.00, CHCl 3 ); lit.…”
Section: Chemical Identification Of the Isolated Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of comparison of the NMR and specific rotation data with the literature, ten known compounds were identified to be (+)‐(7 S ,11 S )‐12‐hydroxysydonic acid ( 2 ), sydonic acid ( 3 ), hydroxysydonic acid ( 4 ), ascotrichic acid ( 5 ), trinorcyclonerodiol‐7,10‐lactone ( 6 ), 5 α ,8 α ‐epidioxyergosta‐6,22‐dien‐3 β ‐ol ( 7 ), cyclo‐( l ‐Leu‐ l ‐Trp) ( 8 ), cyclo‐( l ‐Trp‐Gly) ( 9 ), cyclo‐( l ‐Phe‐ l ‐Leu) ( 10 ), and cyclo‐( l ‐Leu‐ l ‐Tyr) ( 11 ) …”
Section: Resultsmentioning
confidence: 99%
“…Besides the above-mentioned three novel compounds (compounds 1, 8, and 9), three known trichomide cyclodepsipeptides were isolated from the PDB medium: destruxin A5 (compound 2) [11], trichomide A (compound 3) [11], and homodestruxin B (compound 4) [11]. Three typical destruxin cyclodepsipeptides, destruxin chlorohydrin (compound 5) [28], roseotoxin B (compound 6) [29], and C (compound 7) [30], and one cyclonerodiol sesquiterpene, ascotrichic acid (compound 10) [31] were isolated from the rice medium. The structures of these compounds were determined by detailed analyses of their spectroscopic data and comparisons with previously published reports.…”
Section: Resultsmentioning
confidence: 99%